Biased beliefs, costly external finance, and firm behavior: A Unified theory - Delong Li; Lei Lu; Congming Mu; Jinqiang Yang (Bank of Finland, 2019)
Overconfidence and overextrapolation are two behavioral biases that are pervasive in human thinking. A long line of research documents that such biases influence business decisions by distorting managers' expected productivity. We propose a new mechanism in which the biases change firms' precautionary motives when external financing is costly, finding that the influences of biases on investment, payouts, and refinancing are stronger for financially weaker firms. Moreover, biased and rational firms display di erential responses to economic booms and busts holding financial positions constant. Our work illustrates that managerial traits, when interacting with imperfect capital markets, drive firm dynamics in business cycles.
URN:NBN:fi:bof-201909101449
Keywords: E32; G31; G32; G35; G41; 330